Lichen as the biological indicator for detection of environmental tobacco smoke (ETS) at the public office building in Selangor, Malaysia - Abas, Azlan; Rasli, Fateen Nabilla; Juhari, Mohammad Lui (Frontiers in Environmental Science, 2024)
Lichens are recognized as highly efficient biological indicators of air pollution. They have been extensively used to detect various types of air pollutants, both from outdoor and indoor sources.Environmental Tobacco Smoke (ETS) is known to be hazardous not only to its consumers but also to passive consumers, particularly within buildings. This study aims to explore the detection of ETS using lichens within a building in Malaysia. The research was conducted in a public building in Selangor, Malaysia, employing the lichen species Usnea misaminensis. The transplanting technique was utilized, and the nicotine concentration and lichen vitality rate were analyzed. The study demonstrated that lichens can serve as effective biological indicators of indoor air pollutants, specifically nicotine. Additionally, a significant negative relationship (r = -0.71) was found between the lichen vitality rate and nicotine concentrations in the lichen samples placed in the building. This indicates that higher nicotine concentrations in the lichens after approximately two months of exposure correspond to lower lichen vitality rates. Research into nicotine detection using lichens may lead to the development of novel monitoring techniques for indoor air quality assessment. Integrating lichen-based sensors into portable monitoring devices or passive sampling systems could provide cost-effective and non-intrusive methods for continuously monitoring nicotine levels in buildings.